Hole transport layer, trans-perovskite solar cell and preparation method

By using a hole transport layer that combines self-assembled molecules and multifunctional passivation molecules in perovskite solar cells, the problem of insufficient interface of the bottom passivation perovskite in the prior art is solved, and the voltage of the device is significantly improved. Fill factor and efficiency.

CN119451388APending Publication Date: 2025-02-14TRINA SOLAR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411560845.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The lack of effective hole transport layer materials in the prior art in perovskite solar cells leads to insufficient interface of passivation of perovskite bottom, affecting the open circuit voltage, filling factor and photoelectric conversion efficiency of the device.

Method used

A hole transport layer that combines self-assembled molecules and passivation molecules. The passivation molecule has two or more functional groups, which can effectively passivate the defects at the bottom of the perovskite absorbing layer and promote hole extraction and transmission.

Benefits of technology

By improving the interface between perovskite and hole transport layer, the open circuit voltage, fill factor and photoelectric conversion efficiency of trans perovskite solar cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451388A_ABST
    Figure CN119451388A_ABST
Patent Text Reader

Abstract

The invention belongs to the photovoltaic field, and particularly relates to a hole transport layer, a trans-perovskite solar cell and a preparation method. The hole transport layer comprises self-assembly molecules and passivation molecules, wherein the chemical formula of the passivation molecules is R1-L-R2; r1 is an electron withdrawing group; r2 is a phosphate group, a silicic acid group or a carboxyl group; l is a C1 to C10 alkylene group, a C6-C14 arylene group, or a 5 to 14 membered heteroarylene group having 1 to 3 heteroatoms selected from the group consisting of N, O and S. The hole transport layer provided by the invention can promote passivation and hole extraction of the bottom interface of the perovskite light absorption layer, so that the open-circuit voltage, the fill factor and the photoelectric conversion efficiency of the trans-perovskite solar cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photovoltaics, and in particular relates to a hole transport layer, an inverse perovskite solar cell and a preparation method thereof. Background Art

[0002] As an emerging type of solar cell, perovskite solar cells have developed very rapidly. In just a few years, their cell conversion efficiency has rapidly exceeded 26% from less than 10%. Due to the adjustable bandgap of perovskite, it can be combined with bottom cells such as crystalline silicon, copper indium gallium selenide, and perovskite to form a stacked cell. In the series stacked cell structure, the wide-bandgap perovskite top cell is responsible for collecting the short-wave light domain of the solar spectrum, and the narrow-bandgap bottom cell absorbs the remaining long-wave light domain, thereby maximizing the use of the solar spectrum and reducing the thermal energy loss of photon energy. The theoretical conversion rate limit can reach 43%. Whether it is a single-junction perovskite cell or a multi-junction cell, its actual efficiency is still a certain distance away from the theoretical limit. How to improve it needs to focus on the optimization of the interface of the perovskite. For trans-pin structure perovskite solar cells, a large number of studies have been conducted on the perovskite surface interface, and a variety of multifunctional passivation molecules have been developed successively, which can not only passivate the dangling bonds on the perovskite surface, but also improve the contact between the perovskite surface and the electron transport layer (C60), forming an energy level structure that is more conducive to carrier transmission. However, there are few studies on the interface modification between perovskite and the bottom hole transport layer, and there is a lack of development of effective materials that promote hole transport and passivate the bottom interface of perovskite.

[0003] The existing technology uses commonly used self-assembled molecules (SAM) as hole transport layers to optimize the bottom interface of perovskite or passivates the bottom interface of perovskite by using passivation molecules alone. However, the design of existing SAM molecules mainly focuses on functional group design for transport performance, and few passivation functional groups are introduced. In addition, there are problems of too many and too large side chains. The excessive steric hindrance will lead to poor anchoring with the bottom, resulting in poor device repeatability and poor contact with the perovskite light absorption layer. Although the use of passivation molecules alone can passivate the bottom defects of the perovskite light absorption layer to a certain extent, commonly used passivation molecules often do not have good transport performance, and even cause energy level mismatch and non-ohmic contact, making the device fill factor abnormal.

[0004] Therefore, there is an urgent need to develop a hole transport layer that can take into account the passivation of the bottom metal oxide defects, the passivation of the bottom interface of the perovskite light-absorbing layer, and the improvement of the hole extraction capacity, thereby improving the open circuit voltage, fill factor and photoelectric conversion efficiency of inverse perovskite solar cells. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a hole transport layer, an inverted perovskite solar cell and a preparation method. The hole transport layer of the present invention has self-assembly molecules and passivation molecules, and the passivation molecules have two or more functional groups. On the one hand, one end of the passivation molecule can fill the anchoring gap of the SAM molecule and anchor with the bottom metal oxide, and the other end can passivate the bottom defect of the perovskite light-absorbing layer; on the other hand, the electronegativity of the entire passivation molecule is toward the end of the perovskite light-absorbing layer, and after the passivation molecule is anchored, the hole can be effectively extracted to the hole transport layer, which is conducive to hole extraction and transmission. Therefore, the hole transport layer of the present invention can realize multiple functions of passivation and transmission, thereby improving the open circuit voltage, fill factor and efficiency of the inverted perovskite solar cell.

[0006] Specifically, the present invention provides a hole transport layer, which includes a self-assembled molecule and a passivation molecule, wherein the chemical formula of the passivation molecule is R1-L-R2; R1 is an electron-withdrawing group; R2 is a phosphate group, a silicate group or a carboxyl group; L is a C1-C10 alkylene group, a C6-C14 arylene group or a 5-14-membered heteroarylene group having 1-3 heteroatoms selected from N, O and S.

[0007] In one or more embodiments, the electron withdrawing group is carboxyl, fluorine, chlorine, bromine, or nitro.

[0008] In one or more embodiments, the C6-C14 arylene group is a phenylene group and / or a naphthylene group.

[0009] In one or more embodiments, when L is phenylene, R1 and R2 are located at the ortho or para position.

[0010] In one or more embodiments, the 5-14 membered heteroarylene group having 1-3 heteroatoms selected from N, O and S is selected from one or more of pyrrolylene, pyridylene and carbazolylene.

[0011] In one or more embodiments, the self-assembling molecule is selected from one or more of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid and 3-mercaptopropionic acid.

[0012] In one or more embodiments, the hole transport layer has a single-layer or double-layer structure. When the hole transport layer is a single-layer, the hole transport layer is a mixed material layer, and the material of the mixed material layer includes the self-assembled molecules and the passivation molecules; when the hole transport layer is a double-layer, the hole transport layer includes a self-assembled molecular layer and a passivation molecular layer, and the material of the self-assembled molecular layer is the self-assembled molecules, and the material of the passivation molecular layer is the passivation molecules.

[0013] In one or more embodiments, in the mixed material layer, the mass ratio of the self-assembling molecules to the passivation molecules is 1:(0.02-50).

[0014] In one or more embodiments, the thickness of the mixed material layer is

[0015] In one or more embodiments, the thickness of the self-assembled molecular layer is

[0016] In one or more embodiments, the thickness of the passivation molecular layer is

[0017] The present invention provides a method for preparing the hole transport layer of the present invention, the method comprising the following steps:

[0018] (1) dissolving the self-assembling molecules in a solvent to obtain a self-assembling molecular solution, depositing the self-assembling molecular solution, and then performing a first annealing to obtain a self-assembling molecular layer; dissolving the passivating molecules in a solvent to obtain a passivating molecular solution, depositing the passivating molecular solution on the self-assembling molecular layer, and then performing a second annealing to obtain a passivating molecular layer; the self-assembling molecular layer and the passivating molecular layer together constitute a hole transport layer; or

[0019] (1') preparing a passivation mixed material solution containing passivation molecules and self-assembling molecules, depositing the passivation mixed material solution, and then annealing it to obtain a mixed material layer, namely, a hole transport layer.

[0020] In one or more embodiments, in step (1), the solvent of the self-assembling molecule solution is selected from one or more of isopropanol, ethanol, methanol and N,N-dimethylacetamide.

[0021] In one or more embodiments, in step (1), the concentration of the self-assembling molecules in the self-assembling molecule solution is 0.1-5 mg / mL.

[0022] In one or more embodiments, in step (1), the self-assembling molecular solution is deposited by spin coating, blade coating, slit coating or immersion.

[0023] In one or more embodiments, in step (1), the first annealing temperature is 70-130°C.

[0024] In one or more embodiments, in step (1), the first annealing time is 5-15 min.

[0025] In one or more embodiments, in step (1), the solvent of the passivation molecule solution is selected from one or more of isopropanol, ethanol, methanol and N,N-dimethylacetamide.

[0026] In one or more embodiments, in step (1), the concentration of the passivation molecule in the passivation molecule solution is 0.1-5 mg / mL.

[0027] In one or more embodiments, in step (1), the passivation molecule solution is deposited by spin coating, blade coating, slit coating or immersion.

[0028] In one or more embodiments, in step (1), the second annealing temperature is 70-130°C.

[0029] In one or more embodiments, in step (1), the second annealing time is 5-15 min.

[0030] In one or more embodiments, in step (1'), the solvent of the passivation mixed substance solution is selected from one or more of isopropanol, ethanol, methanol and N,N-dimethylacetamide.

[0031] In one or more embodiments, in step (1'), the concentration of the self-assembling molecules in the passivation mixed substance solution is 0.1-5 mg / mL.

[0032] In one or more embodiments, in step (1'), the concentration of the passivating molecules in the passivating mixed substance solution is 0.1-5 mg / mL.

[0033] In one or more embodiments, in step (1'), the passivation mixed material solution is deposited by spin coating, doctor blade coating, slit coating or dipping.

[0034] In one or more embodiments, in step (1'), the annealing temperature is 70-130°C.

[0035] In one or more embodiments, in step (1'), the annealing time is 5-15 min.

[0036] In one or more embodiments, in step (1), after the first annealing, cleaning and supplementary annealing are performed in sequence to obtain a self-assembled molecular layer.

[0037] In one or more embodiments, in step (1), after the second annealing, cleaning and supplementary annealing are performed in sequence to obtain a passivation molecular layer.

[0038] In one or more embodiments, in step (1'), after annealing, cleaning and additional annealing are performed in sequence to obtain a mixed material layer.

[0039] In one or more embodiments, the solvent used for cleaning is selected from one or more of isopropanol, ethanol, methanol and N,N-dimethylacetamide.

[0040] In one or more embodiments, the temperature of the supplementary annealing is 70-130°C.

[0041] In one or more embodiments, the supplementary annealing time is 3-10 min.

[0042] The present invention provides an inverted perovskite solar cell comprising the hole transport layer of the present invention.

[0043] In one or more embodiments, the inverse perovskite solar cell includes a metal oxide layer, a hole transport layer, a perovskite light absorbing layer, and an electron transport layer in sequence from a thickness direction.

[0044] The present invention provides a method for preparing the inverse perovskite solar cell of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 (a) is a diagram showing the mechanism of action of inactivating molecules according to some embodiments of the present invention.

[0046] Figure 1 (b) is a diagram showing the mechanism of action of Example 1 of the present invention in which the passivating molecule is 4-phosphobenzoic acid.

[0047] Figure 1 (c) is a diagram showing the mechanism of action of the passivating molecule in Example 2 of the present invention, which is p-nitrobenzoic acid.

[0048] Figure 1 (d) is a diagram showing the mechanism of action of Example 3 of the present invention in which the passivating molecule is 4-trifluoromethylbenzoic acid. DETAILED DESCRIPTION

[0049] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0050] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0051] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0052] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0053] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0054] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0055] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0056] The present invention provides a hole transport layer, which may include self-assembly molecules and passivation molecules, wherein the chemical formula of the passivation molecules may be R1-L-R2; R1 may be an electron-withdrawing group; R2 may be a phosphate group, a silicic acid group or a carboxyl group; L may be a C1-C10 alkylene group, a C6-C14 arylene group or a 5-14-membered heteroarylene group having 1-3 heteroatoms selected from N, O and S. In the present invention, the groups of the passivation molecules are anchored to the conductive substrate and the perovskite light-absorbing layer respectively, the group anchored to the perovskite light-absorbing layer is the R1 electron-withdrawing group, the group anchored to the conductive substrate is the R2 group (anchoring group), and the functional groups at both ends are connected by L (connecting group). In the present invention, the introduction of the passivation molecule can improve the poor anchoring problem caused by the relatively large steric hindrance effect of the SAM molecule. Since the size of the passivation molecule is small (small steric hindrance), it can be filled in the anchoring gap of the SAM molecule, one end is combined with the bottom metal oxide layer through the anchoring group, and the electron-withdrawing group at the other end is in contact with the bottom of the perovskite light-absorbing layer, thereby avoiding the non-radiative recombination caused by the defects of the direct contact between the perovskite structure material and the bottom metal oxide layer and the efficiency reduction caused by the energy level mismatch; secondly, the direct contact between the electron-withdrawing group and the perovskite light-absorbing layer can passivate the dangling bond at the bottom of the perovskite light-absorbing layer to a certain extent (by adsorption or bonding with the perovskite structure material). Pb combination, etc.), reducing interface defects and improving the quality of the perovskite light-absorbing layer; at the same time, the electronegativity of the electron-withdrawing group itself determines that the electrons in the passivation molecule will preferentially transfer to the electron-withdrawing group, and the overall molecular electrostatic potential is that the electron cloud density of the top electron-withdrawing group is large, and the electron cloud density of the connecting group is small. Therefore, when the passivation molecule is introduced into the structure of the metal oxide layer / hole transport layer / perovskite light-absorbing layer, the electrons will transfer from the metal oxide layer to the hole transport layer and then to the perovskite light-absorbing layer, and the holes will transfer from the perovskite light-absorbing layer to the hole transport layer and then to the metal oxide layer. This transport-promoting advantage can effectively promote the improvement of the filling factor of the perovskite solar cell, thereby improving the device efficiency.

[0057] In the present invention, the electron withdrawing group may be a carboxyl group (-COOH), a fluorine group (-F), a chlorine group (-Cl), a bromine group (-Br) or a nitro group (-NO2).

[0058] In the present invention, the C6-C14 arylene group may be a phenylene group and / or a naphthylene group. In the present invention, when L is a phenylene group, R1 and R2 may be located at the ortho position or the para position.

[0059] In the present invention, the 5-14 membered heteroarylene group having 1-3 heteroatoms selected from N, O and S may be one or more selected from pyrrolylene, pyridylene and carbazolylene. In the present invention, the self-assembling molecule may be one or more selected from [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) and 3-mercaptopropionic acid (3-MPA).

[0060] Figure 1 (a) shows that the passivation molecule is located between the metal oxide layer and the bottom interface of the top perovskite light-absorbing layer. It mainly fills the gaps where the SAM molecules are anchored. The passivation molecule includes an anchoring group (R2) close to the metal oxide, an electron-withdrawing group (R1) close to the perovskite end, and a connecting group (L) connecting the two ends.

[0061] Figure 1 In (b), the successfully anchored 4-phosphobenzoic acid occupies the gap between SAM macromolecules and is anchored to the metal oxide through the phosphate group. The carboxyl group coordinates with the Pb at the bottom of the perovskite light-absorbing layer to passivate the defects. At the same time, the carboxyl group, as a strongly electronegative group, effectively promotes the aggregation of charges on the benzene ring to the carboxyl group, which is beneficial to the downward transfer of holes. Through this passivation molecule, the bottom of the perovskite light-absorbing layer is passivated and charge transfer is promoted.

[0062] Figure 1 In (c), the successfully anchored p-nitrobenzoic acid occupies the gap between SAM macromolecules and is anchored to the metal oxide through the carboxyl group. The defects are passivated by coordinating with the Pb at the bottom of the perovskite light-absorbing layer through the p-nitro group. At the same time, the nitrate group, as a strongly electronegative group, effectively promotes the aggregation of charges on the benzene ring to the nitrate group, which is beneficial to the downward transfer of holes. Through this passivation molecule, the bottom of the perovskite light-absorbing layer is passivated and charge transfer is promoted.

[0063] Figure 1 In (d), the successfully anchored 4-trifluoromethylbenzoic acid occupies the gap between the SAM macromolecules and is anchored to the metal oxide through the carboxyl group; it acts on the bottom of the perovskite light-absorbing layer through the para-fluorine. At the same time, fluorine, as a strong electronegative group, effectively promotes the aggregation of charges on the benzene ring to fluorine, which is beneficial to the downward transfer of holes; through this passivation molecule, the bottom of the perovskite light-absorbing layer is passivated and charge transfer is promoted.

[0064] In the present invention, the hole transport layer may be a single layer or a double layer structure.

[0065] In the present invention, when the hole transport layer is a single layer, the hole transport layer may be a mixed material layer, and the material of the mixed material layer may include self-assembly molecules and passivation molecules.

[0066] In the present invention, when the hole transport layer is a double layer, the hole transport layer may include a self-assembled molecular layer and a passivation molecular layer. The material of the self-assembled molecular layer may be self-assembled molecules, and the material of the passivation molecular layer may be passivation molecules.

[0067] In the present invention, in the mixed material layer, the mass ratio of the self-assembling molecules to the passivating molecules can be 1:(0.02-50), for example, 1:0.02, 1:0.1, 1:0.5, 1:1, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50. In the present invention, controlling the mass ratio of the self-assembling molecules to the passivating molecules within the above range is beneficial to improving the open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of the inverse perovskite solar cell.

[0068] In the present invention, the thickness of the mixed material layer can be For example

[0069] In the present invention, the thickness of the self-assembled molecular layer can be For example

[0070] In the present invention, the thickness of the passivation molecular layer can be For example

[0071] The present invention provides a method for preparing the hole transport layer of the present invention, the method comprising the following steps:

[0072] (1) dissolving the self-assembling molecules in a solvent to obtain a self-assembling molecular solution, depositing the self-assembling molecular solution, and then performing a first annealing to obtain a self-assembling molecular layer; dissolving the passivating molecules in a solvent to obtain a passivating molecular solution, depositing the passivating molecular solution on the self-assembling molecular layer, and then performing a second annealing to obtain a passivating molecular layer; the self-assembling molecular layer and the passivating molecular layer together constitute a hole transport layer; or

[0073] (1') preparing a passivation mixed material solution containing passivation molecules and self-assembling molecules, depositing the passivation mixed material solution, and then annealing it to obtain a mixed material layer, namely, a hole transport layer.

[0074] In step (1), the solvent of the self-assembling molecular solution can be one or more selected from the group consisting of (IPA), ethanol (EtOH), methanol (Methanol) and N,N-dimethylacetamide (DMF).

[0075] In step (1), the concentration of the self-assembled molecules in the self-assembled molecule solution can be 0.1-5 mg / mL, such as 0.1 mg / mL, 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3.0 mg / mL, 3.5 mg / mL, 4.0 mg / mL, 4.5 mg / mL, 5.0 mg / mL. In the present invention, the concentration of the self-assembled molecules is controlled within the above range, which is beneficial to improving the open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of the inverse perovskite solar cell.

[0076] In step (1), the self-assembling molecular solution can be deposited by spin coating, blade coating, slit coating or immersion.

[0077] In step (1), the first annealing temperature can be 70-130°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C.

[0078] In step (1), the first annealing time can be 5-15 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min.

[0079] In step (1), after the first annealing, cleaning and additional annealing may be performed in sequence to obtain a self-assembled molecular layer.

[0080] In step (1), the solvent of the passivation molecule solution may be one or more of isopropyl alcohol (IPA), ethanol (EtOH), methanol (Methanol) and N,N-dimethylacetamide (DMF).

[0081] In step (1), the concentration of the passivating molecule in the passivating molecule solution can be 0.1-5 mg / mL, such as 0.1 mg / mL, 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3.0 mg / mL, 3.5 mg / mL, 4.0 mg / mL, 4.5 mg / mL, 5.0 mg / mL. In the present invention, the concentration of the passivating molecule is controlled within the above range, which is beneficial to improving the open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of the inverse perovskite solar cell.

[0082] In step (1), the passivation molecule solution can be deposited by spin coating, scraper coating, slit coating or immersion.

[0083] In step (1), the solvent used for cleaning can be one or more of isopropyl alcohol (IPA), ethanol (EtOH), methanol (Methanol) and N,N-dimethylacetamide (DMF).

[0084] In step (1), the second annealing temperature can be 70-130°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C.

[0085] In step (1), the second annealing time can be 5-15 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min.

[0086] In step (1), after the second annealing, cleaning and additional annealing may be performed in sequence to obtain a passivation molecular layer.

[0087] In step (1'), the solvent of the passivation mixed substance solution may be one or more selected from isopropanol, ethanol, methanol and N,N-dimethylacetamide.

[0088] In step (1'), the concentration of the self-assembled molecules in the passivation mixed substance solution can be 0.1-5 mg / mL, such as 0.1 mg / mL, 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3.0 mg / mL, 3.5 mg / mL, 4.0 mg / mL, 4.5 mg / mL, 5.0 mg / mL. In the present invention, controlling the concentration of the self-assembled molecules within the above range is beneficial to improving the open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of the inverse perovskite solar cell.

[0089] In step (1'), the concentration of the passivation molecule in the passivation mixed substance solution can be 0.1-5 mg / mL, such as 0.1 mg / mL, 0.5 mg / mL, 1.0 mg / mL, 1.5 mg / mL, 2 mg / mL, 2.5 mg / mL, 3.0 mg / mL, 3.5 mg / mL, 4.0 mg / mL, 4.5 mg / mL, 5.0 mg / mL. In the present invention, controlling the concentration of the passivation molecule within the above range is beneficial to improving the open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of the inverse perovskite solar cell.

[0090] In step (1'), the passivation mixed substance solution can be deposited by spin coating, blade coating, slit coating or immersion.

[0091] In step (1'), the annealing temperature may be 70-130°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C.

[0092] In step (1'), the annealing time can be 5-15 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min.

[0093] In step (1'), after annealing, cleaning and additional annealing may be performed in sequence to obtain a mixed material layer.

[0094] In the present invention, the solvent used for cleaning can be one or more selected from isopropanol, ethanol, methanol and N,N-dimethylacetamide.

[0095] In the present invention, the temperature of the supplementary annealing may be 70-130°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, or 130°C.

[0096] In the present invention, the time for supplementary annealing can be 3-10 min, for example, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, and 10 min.

[0097] In step (1) of the present invention, cleaning and supplementary annealing may be performed sequentially only after the first annealing; cleaning and supplementary annealing may be performed sequentially only after the second annealing; or cleaning and supplementary annealing may be performed sequentially after both the first annealing and the second annealing.

[0098] In step (1) of the present invention, the solvents used for cleaning after the first annealing and cleaning after the second annealing may be the same or different.

[0099] In step (1) of the present invention, when supplementary annealing is performed after the first annealing and supplementary annealing is performed after the second annealing, the temperatures of the supplementary annealing may be the same or different.

[0100] In step (1) of the present invention, when supplementary annealing is performed after the first annealing and supplementary annealing is performed after the second annealing, the time of the supplementary annealing can be the same or different.

[0101] The present invention provides an inverted perovskite solar cell, which comprises the hole transport layer of the present invention.

[0102] In the present invention, the inverted perovskite solar cell may include a metal oxide layer, a hole transport layer, a perovskite light absorption layer and an electron transport layer in sequence from the thickness direction. In the present invention, the metal oxide layer may be one or more selected from indium tin oxide (ITO), indium zinc oxide (IZO), tungsten-doped indium oxide (IWO), cerium-doped indium oxide (ICO), In2O3, fluorine-doped indium oxide (FTO), gallium-doped zinc oxide (GZO) and aluminum-doped zinc oxide (AZO).

[0103] In the present invention, the thickness of the metal oxide layer can be 50-150 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, and 150 nm.

[0104] In the present invention, the thickness of the perovskite light absorbing layer can be 200-2000nm, for example, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1200nm, 1400nm, 1500nm, 1600nm, 1800nm, 2000nm.

[0105] In the present invention, the perovskite light absorbing layer may include a perovskite structure material, the chemical formula of the perovskite structure material may be an ABX3 structure, wherein the A-site ion may be a cesium ion (Cs + ), rubidium ion (Rb + ), methylamine ion (CH3NH3 + , MA) and formamidinium ion (CH(NH2)2 + , FA), the B-site ion may be a lead ion (Pb 2+ ) and / or tin ions (Sn 2+ ), the X-site ion may be selected from iodide ions (I - ), bromide ion (Br - ) and chloride ions (Cl - )

[0106] In the present invention, the thickness of the electron transport layer may be 5-60 nm, for example, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, or 60 nm.

[0107] In the present invention, the electron transport layer may be one of C60, a fullerene derivative, BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline), SnO2 or TiO2.

[0108] In the present invention, the fullerene diffractor may be PCBM or indene-C60 bisadduct (ICBA)

[0109] In the present invention, the inverted perovskite solar cell may be an inverted single-junction perovskite solar cell or an inverted tandem perovskite solar cell.

[0110] In the present invention, the inverted single-junction perovskite solar cell may include a conductive substrate, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer and a metal electrode in sequence from the thickness direction, and the conductive substrate may include a substrate and a metal oxide layer in sequence from the thickness direction.

[0111] In the present invention, the inverted single-junction perovskite solar cell may further include a hole blocking layer, and the hole blocking layer may be located between the electron transport layer and the metal electrode.

[0112] In the present invention, the thickness of the metal oxide layer in the conductive substrate can be 50-150 nm, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm.

[0113] In the present invention, the thickness of the metal electrode can be 60-800 nm, for example, 60 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, and 1000 nm.

[0114] In the present invention, the metal electrode may be Cu, Ag, Au or carbon.

[0115] In the present invention, the inverted stacked perovskite solar cell may include a bottom electrode, a bottom battery, an interconnection layer, a hole transport layer, a perovskite light absorption layer, an electron transport layer and a top electrode in sequence from the thickness direction, and the interconnection layer may be a metal oxide layer.

[0116] In the present invention, the inverted stacked perovskite solar cell may further include a hole blocking layer, and the hole blocking layer may be located between the electron transport layer and the top electrode.

[0117] In the present invention, the thickness of the interconnect layer may be 5-50 nm, for example, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, or 50 nm.

[0118] The present invention provides a method for preparing an inverted single-junction perovskite solar cell of the present invention, the method comprising the following steps:

[0119] (1) depositing a hole transport layer on the surface of a conductive substrate;

[0120] (2) depositing a perovskite light absorbing layer on the surface of the hole transport layer;

[0121] (3) depositing an electron transport layer on the surface of the perovskite light absorbing layer;

[0122] (4) A metal electrode is deposited on the surface of the electron transport layer to obtain an inverted single-junction perovskite solar cell.

[0123] In the present invention, the deposition method of the perovskite light absorbing layer can be spin coating, blade coating, slit coating, spray coating, immersion or evaporation.

[0124] In the present invention, the electron transport layer can be deposited by spin coating, blade coating, slit coating, spray coating or evaporation.

[0125] In the present invention, the metal electrode can be deposited by evaporation or screen printing.

[0126] The present invention provides a method for preparing an inverted stacked perovskite solar cell of the present invention, the method comprising the following steps:

[0127] (1) Depositing the bottom electrode and interconnect layer on both sides of the bottom cell;

[0128] (2) depositing a hole transport layer on the surface of the interconnect layer;

[0129] (3) depositing a perovskite light absorbing layer on the surface of the hole transport layer;

[0130] (4) depositing an electron transport layer on the surface of the perovskite light absorbing layer;

[0131] (5) A top electrode is deposited on the surface of the electron transport layer to obtain an inverted stacked perovskite solar cell.

[0132] Compared with the prior art, the present invention has the following beneficial effects: the present invention can effectively passivate bottom defects, reduce interface defects of the perovskite light-absorbing layer, and at the same time improve the hole extraction capability, improve the fill factor (FF) of the battery, and improve the photoelectric conversion efficiency of the inverse perovskite solar cell.

[0133] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0134] Example 1

[0135] In this embodiment, an inverted perovskite solar cell is prepared, and the specific steps are as follows:

[0136] (1) using deionized water to clean the ITO conductive glass substrate, then placing it in isopropanol for ultrasonic treatment for 30 minutes, blowing the residual isopropanol from the ultrasonicated ITO substrate with nitrogen, and then placing it in an ultraviolet ozone cleaning machine for treatment for 15 minutes to obtain a clean ITO conductive glass substrate;

[0137] (2) Dissolve Me-4PACz in isopropyl alcohol (IPA) to obtain a 1 mg / mL self-assembled molecule (SAM) solution, and spin-coat the self-assembled molecule solution on a clean ITO conductive glass substrate, wherein the spin coating speed is 4000 r / min and the spin coating acceleration is 1000 r / min. 2 , the spin coating time is 30s, and after the spin coating is completed, it is annealed on a hot plate at 100°C for 10min. After annealing, it is washed once with 200μL of isopropanol under the same spin coating parameters, and then annealed at 100°C for 5min to obtain a self-assembled molecular layer; 4-phosphorylbenzoic acid is dissolved in IPA to obtain a 1mg / mL passivation molecule solution, and the passivation molecule solution is spin-coated on the surface of the self-assembled molecular layer, wherein the spin coating speed is 4000r / min and the spin coating acceleration is 1000r / min 2 , the spin coating time is 30s, and after the spin coating is completed, it is annealed at 100℃ for 10min. After annealing, it is cleaned with IPA under the same spin coating parameters, and then annealed at 100℃ for 5min to obtain a passivation molecular layer; the self-assembled molecular layer and the passivation molecular layer together constitute a hole transport layer;

[0138] (3) The substrate coated with SAM and passivation molecules was transferred to a nitrogen glove box, and the theoretical chemical formula of Cs was generated in the nitrogen glove box. 0.05 (FA 0.77 MA 0.23 )0.95Pb(I 0.77 Br 0.23 )3, CsI, FAI, MAI, PbI2, and PbBr2 were weighed respectively, and dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (the volume ratio of DMF and DMSO was 4:1) to obtain a perovskite precursor solution with a theoretical concentration of 1.5 mol / L of perovskite structure substances; in a glove box, the perovskite precursor solution was spin-coated on the surface of the passivation molecular layer by a one-step spin coating method, wherein the spin coating speed was 5000 r / min and the spin coating acceleration was 1000 r / min 2 , the rotation time is 30s, and at the last 10s, 200μL of chlorobenzene (CB) is added as an anti-solvent to prepare a perovskite light-absorbing layer, which is annealed on a hot plate at 100°C for 25min to obtain a perovskite light-absorbing layer with a thickness of 600nm;

[0139] (4) The substrate with the deposited perovskite light-absorbing layer is transferred to a thermal evaporation device, and 30 nm of C60 is evaporated as an electron transport layer, 10 nm of BCP is evaporated as a hole blocking layer, and 200 nm of Cu is evaporated as a back electrode. At this time, an inverted perovskite solar cell is obtained.

[0140] Example 2

[0141] The other conditions of this embodiment are the same as those of embodiment 1, except that the passivating molecule in this embodiment is replaced by p-nitrobenzoic acid from 4-phosphobenzoic acid.

[0142] Example 3

[0143] The other conditions of this embodiment are the same as those of embodiment 1, except that the passivation molecule in this embodiment is replaced by 4-trifluoromethylbenzoic acid from 4-phosphobenzoic acid.

[0144] Example 4

[0145] The other conditions of this embodiment are the same as those of embodiment 1, except that step (2) of this embodiment is as follows: dissolving Me-4PACz in IPA to obtain a 2 mg / mL self-assembled molecule (SAM) solution, dissolving 4-phosphorylbenzoic acid in IPA to obtain a 2 mg / mL passivation molecule solution, then mixing the self-assembled molecule solution and the passivation molecule solution in equal volumes, and ultrasonically vibrating for 10 minutes to obtain a passivation mixed substance solution with a Me-4PACz concentration of 1 mg / mL and a 4-phosphorylbenzoic acid concentration of 1 mg / mL; and spin coating the passivation mixed substance solution on a clean ITO conductive glass substrate, wherein the spin coating speed is 4000 r / min and the spin coating acceleration is 1000 r / min. 2 , spin coating time is 30s, after spin coating, annealing is performed on a hot plate at 100°C for 10min, after annealing, it is washed once with 200μL isopropanol under the same spin coating parameters, and then annealing is performed at 100°C for 5min to obtain a mixed material layer, which is the hole transport layer.

[0146] Comparative Example 1

[0147] The other conditions of this comparative example are the same as those of Example 1, except that step (2) of this comparative example is: Me-4PACz is dissolved in isopropanol to obtain a 1 mg / mL self-assembled molecule (SAM) solution, and the self-assembled molecule solution is spin-coated on a clean ITO conductive glass substrate, wherein the spin-coating speed is 4000 r / min and the spin-coating acceleration is 1000 r / min. 2 , spin coating time 30s, annealing on a hot plate at 100℃ for 10min after spin coating, washing with 200μL isopropanol under the same spin coating parameters, and then annealing at 100℃ for 5min to obtain a self-assembled molecular layer, which is the hole transport layer.

[0148] Comparative Example 2

[0149] The other conditions of this comparative example are the same as those of Example 1, except that step (2) of this comparative example is: spin coating a 20 mg / mL NiOx nanocrystal solution dissolved in a deionized water solution on a clean ITO conductive glass substrate, wherein the spin coating speed is 4000 r / min and the spin coating acceleration is 1000 r / min. 2 , the spin coating time is 30s, and after the spin coating is completed, annealing is performed on a hot plate at 100°C for 10min to obtain a NiOx layer; 4-phosphobenzoic acid is dissolved in IPA to obtain a 1mg / mL passivation molecule solution, and the passivation molecule solution is spin-coated on the surface of the NiOx layer, wherein the spin coating speed is 4000r / min and the spin coating acceleration is 1000r / min 2 , spin coating time is 30s, annealing is performed at 100℃ for 10min after spin coating, cleaning is performed once with IPA under the same spin coating parameters, and then annealing is performed at 100℃ for 5min to obtain a passivation molecular layer; the NiOx layer and the passivation molecular layer together constitute a hole transport layer.

[0150] Comparative Example 3

[0151] The other conditions of this comparative example are the same as those of Example 1, except that in this comparative example, the passivating molecule is replaced by phenylphosphoric acid from 4-phosphobenzoic acid.

[0152] Comparative Example 4

[0153] The other conditions of this comparative example are the same as those of Example 1, except that in this comparative example, the passivating molecule is replaced by phenylethylamine from 4-phosphorylbenzoic acid.

[0154] Test Example 1

[0155] Performance test of inverse perovskite solar cells: At 25°C and AM 1.5G standard solar spectrum, a solar simulator was used to set the voltage range to -0.1V to 1.3V, and the current output of the inverse perovskite solar cells prepared in Examples 1-4 and Comparative Examples 1-4 at different voltages was tested, and the corresponding current-voltage (IV) characteristic curves were plotted, where the cell surface area was 0.049cm 2 , the incident light power (Pin) is 100mW / cm 2 The performance (open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency) of the inverse perovskite solar cells prepared in Examples 1-4 and Comparative Examples 1-4 were obtained according to the characteristic curves.

[0156] (1) Open circuit voltage (Voc): The voltage value corresponding to when the current is equal to zero.

[0157] (2) Short-circuit current density (Jsc): The current value when the voltage is zero is the short-circuit current (Isc), and the current per unit battery surface area is the short-circuit current density.

[0158] (3) Fill factor (FF): The ratio of the maximum output power (Pmax) of the battery to the product of the open circuit voltage and the short circuit current. The calculation formula is (Pmax / Voc*Isc), where the maximum power point is the point where the battery output power reaches its maximum value.

[0159] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin)*100%.

[0160] The test results of the open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of the inverse perovskite solar cells prepared in Examples 1-4 and Comparative Examples 1-4 are shown in Table 1.

[0161] Table 1: Open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of the inverse perovskite solar cells prepared in Examples 1-4 and Comparative Examples 1-4

[0162] Voc(V) <![CDATA[Jsc(mA / cm 2 )]]> FF(%) PCE(%) Example 1 1.200 21.0 81.3 20.5 Example 2 1.203 21.1 80.4 20.4 Example 3 1.197 21.4 82.3 21.0 Example 4 1.207 21.0 80.6 20.5 Comparative Example 1 1.194 20.7 79.1 19.5 Comparative Example 2 1.150 20.4 74.0 17.4 Comparative Example 3 1.180 20.6 78.6 19.1 Comparative Example 4 1.91 20.6 79.8 19.5

Claims

1. A hole transport layer, characterized in that: The hole transport layer includes self-assembly molecules and passivation molecules, and the chemical formula of the passivation molecules is R1-L-R2; R1 is an electron-withdrawing group; R2 is a phosphate group, a silicate group or a carboxyl group; L is a C1-C10 alkylene group, a C6-C14 arylene group, or a 5-14-membered heteroarylene group having 1-3 heteroatoms selected from N, O and S.

2. The hole transport layer according to claim 1, characterized in that The hole transport layer has one or more of the following characteristics: The electron-withdrawing group is carboxyl, fluorine, chlorine, bromine or nitro; The C6-C14 arylene group is a phenylene group and / or a naphthylene group; when L is a phenylene group, R1 and R2 are located at the ortho position or the para position; The 5-14 membered heteroarylene group having 1-3 heteroatoms selected from N, O and S is selected from one or more of pyrrolylene, pyridylene and carbazolylene; The self-assembling molecules are selected from one or more of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid and 3-mercaptopropionic acid.

3. The hole transport layer according to claim 1, characterized in that The hole transport layer has a single-layer or double-layer structure. When the hole transport layer is a single-layer, the hole transport layer is a mixed material layer, and the material of the mixed material layer includes the self-assembled molecules and the passivation molecules; when the hole transport layer is a double-layer, the hole transport layer includes a self-assembled molecule layer and a passivation molecule layer, and the material of the self-assembled molecule layer is the self-assembled molecules, and the material of the passivation molecule layer is the passivation molecules.

4. The hole transport layer according to claim 3, characterized in that The hole transport layer has one or more of the following characteristics: In the mixed material layer, the mass ratio of the self-assembling molecules to the passivation molecules is 1:(0.02-50); The thickness of the mixed material layer is The thickness of the self-assembled molecular layer is The thickness of the passivation molecular layer is 5. A method for preparing the hole transport layer according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: (1) dissolving the self-assembling molecules in a solvent to obtain a self-assembling molecular solution, depositing the self-assembling molecular solution, and then performing a first annealing to obtain a self-assembling molecular layer; dissolving the passivating molecules in a solvent to obtain a passivating molecular solution, depositing the passivating molecular solution on the self-assembling molecular layer, and then performing a second annealing to obtain a passivating molecular layer; the self-assembling molecular layer and the passivating molecular layer together constitute a hole transport layer; or (1') preparing a passivation mixed material solution containing passivation molecules and self-assembling molecules, depositing the passivation mixed material solution, and then annealing it to obtain a mixed material layer, namely, a hole transport layer.

6. The method according to claim 5, characterized in that The method has one or more of the following features: In step (1), the solvent of the self-assembling molecular solution is selected from one or more of isopropanol, ethanol, methanol and N,N-dimethylacetamide; In step (1), the concentration of the self-assembling molecules in the self-assembling molecule solution is 0.1-5 mg / mL; In step (1), the self-assembling molecular solution is deposited by spin coating, blade coating, slit coating or immersion; In step (1), the first annealing temperature is 70-130°C; In step (1), the first annealing time is 5-15 min; In step (1), the solvent of the passivation molecule solution is selected from one or more of isopropanol, ethanol, methanol and N,N-dimethylacetamide; In step (1), the concentration of the passivation molecule in the passivation molecule solution is 0.1-5 mg / mL; In step (1), the passivation molecule solution is deposited by spin coating, blade coating, slit coating or immersion; In step (1), the second annealing temperature is 70-130°C; In step (1), the second annealing time is 5-15 min; In step (1'), the solvent of the passivation mixed substance solution is selected from one or more of isopropanol, ethanol, methanol and N,N-dimethylacetamide; In step (1'), the concentration of the self-assembling molecules in the passivation mixed substance solution is 0.1-5 mg / mL; In step (1'), the concentration of the passivation molecule in the passivation mixed substance solution is 0.1-5 mg / mL; In step (1'), the passivation mixed substance solution is deposited by spin coating, blade coating, slit coating or immersion; In step (1'), the annealing temperature is 70-130°C; In step (1'), the annealing time is 5-15 min.

7. The method according to claim 5, characterized in that The method has one or more of the following features: In step (1), after the first annealing, cleaning and supplementary annealing are performed in sequence to obtain a self-assembled molecular layer; In step (1), after the second annealing, cleaning and supplementary annealing are performed in sequence to obtain a passivation molecular layer; In step (1'), after annealing, cleaning and additional annealing are performed in sequence to obtain a mixed material layer.

8. The method according to claim 7, characterized in that The method has one or more of the following features: The solvent used for cleaning is selected from one or more of isopropanol, ethanol, methanol and N,N-dimethylacetamide; The temperature of the supplementary annealing is 70-130°C; The time of the supplementary annealing is 3-10 min.

9. An inverted perovskite solar cell, characterized in that: The inverse perovskite solar cell comprises the hole transport layer according to any one of claims 1 to 4.

10. The inverted perovskite solar cell according to claim 9, characterized in that: The inverted perovskite solar cell comprises a metal oxide layer, a hole transport layer, a perovskite light absorption layer and an electron transport layer in sequence from the thickness direction.